On the usage of sorting networks to control greenhouse climatic factors. (February 2018) - López Ramírez, Blanca C; Guzmán, Giovanni; Alhalabi, Wadee; Cruz-Cortés, Nareli; Torres-Ruiz, Miguel; Moreno-Ibarra, Marco
The goal of this article is the application of a non-adaptive classification algorithm to support the variable management process for internal climate control. The protected agriculture has given many advantages for the care and improvement in the production of almost any food. This work is focused on improving a control system for climate variables. The decision for activating an actuator for the correct care of the crop is very important. A sorting network technique with predefined compare–interchange operations and designed to order data very efficiently is proposed. This approach has been applied to the process of handling actuators within a control system. An advantage of using the sorting networks is that it has an inflexibility when processing a data list; it always takes the same units of time and is executed in the same number of operations for an input size of n . Sorting network–based applications are scarce in the state-of-the-art because there are not many techniques that are effective for sorting very small data sizes. The use of sorting networks in the process of assessing the determination of actuators is proposed. This operation is scheduled in the design of control and performed at each reading back data.